AN ANALYSIS OF TEACHER'S QUESTIONING STRATEGIES IN CLASSROOM INTERACTION - Andi Surya Lestari; Sukmawati Yasim; Nurul Imansari (elstic : english language linguistics culture, 2022)
The purpose of this study was to analyze the questioning strategies used by theteacher in class interaction and the teacher's preference for using questioningstrategies. The approach used in this research is qualitative. The subjects of thisstudy were two English teachers at SMPN 5 Majene. The subjects of this studywere determined using purposive sampling technique. For data collection in thisstudy used instruments such as classroom observations using checklistobservations and video recording and interviews using a voice recorder. Theresults of this study indicate that the teacher uses knowledge questions andcomprehension questions in the classroom. Based on the results of the analysis ofthis study, the teacher also explained that questioning strategies are very important,especially the teacher uses a questioning strategy to measure the extent of students'understanding and abilities during learning.